2016
DOI: 10.3390/en9070478
|View full text |Cite
|
Sign up to set email alerts
|

Slide Valves for Single-Screw Expanders Working Under Varied Operating Conditions

Abstract: This paper fully describes the working principle of slide valves in single-screw expanders (SSEs). A geometric analysis of suction and volume ratio slide valves is presented to determine the relations between volume ratio, suction closure volume, discharge opening volume and slide valves displacement. An organic Rankine cycle (ORC) thermodynamic model with SSE integrated with slide valves is developed to analyze the power output of SSE and the net power output of ORC system and variation law of slide valves di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Liu et al [48] and Wang et al [103] proposed semi-empirical models for optimizing the built-in volume ratio of TSCs with slide valves for refrigeration applications and heat pump applications, respectively. Wu et al [104] further analyzed the relations between volume ratio, suction closure volume, discharge opening volume, and the displacement of the suction and volume ratio slide valves for a SSE used in an ORC system.…”
Section: Control Of Capacity and Built-in Volume Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [48] and Wang et al [103] proposed semi-empirical models for optimizing the built-in volume ratio of TSCs with slide valves for refrigeration applications and heat pump applications, respectively. Wu et al [104] further analyzed the relations between volume ratio, suction closure volume, discharge opening volume, and the displacement of the suction and volume ratio slide valves for a SSE used in an ORC system.…”
Section: Control Of Capacity and Built-in Volume Ratiomentioning
confidence: 99%
“…Wu et al [150] concluded that the optimal built-in volume ratio was not the bigger the better when SSE worked at high pressure ratio condition, because suction pressure loss also increased with the increase of built-in volume ratio. The [104] further presented that adopting slide valves can effectively improve the power output of the SSE and the net power output of the ORC system. Bianchi et al [149].…”
Section: Orc Systemmentioning
confidence: 99%